Australian public knowledge of Islam - Dunn, Kevin M. (Studia islamika, 2005)
This article outlines the extent and nature of the Australian peoples' knowledge of Islam. Knowledge of Islam and contact with can have dramatic and positive effects upon Western Islamophobia and tolerance. (Studia Islam/DÜI-NIAS-Han)